White Paper on studying the safety of the childhood immunization schedule in the Vaccine Safety Datalink. (15th February 2016) - Glanz, Jason M.; Newcomer, Sophia R.; Jackson, Michael L.; Omer, Saad B.; Bednarczyk, Robert A.; Shoup, Jo Ann; DeStefano, Frank; Daley, Matthew F.; ,; ,; ,; Goddard, Kristin; et al.
Abstract: While the large majority of parents in the U.S. vaccinate their children according to the recommended immunization schedule, some parents have refused or delayed vaccinating, often citing safety concerns. In response to public concern, the U.S. Institute of Medicine (IOM) evaluated existing research regarding the safety of the recommended immunization schedule. The IOM concluded that although available evidence strongly supported the safety of the currently recommended schedule as a whole, additional observational research was warranted to compare health outcomes between fully vaccinated children and those on a delayed or alternative schedule. In addition, the IOM identified the Vaccine Safety Datalink (VSD) as an important resource for conducting this research. Guided by the IOM findings, the Centers for Disease Control and Prevention (CDC) commissioned a White Paper to assess how the VSD could be used to study the safety of the childhood immunization schedule. Guided by subject matter expert engagement, the resulting White Paper outlines a 4 stage approach for identifying exposure groups of undervaccinated children, presents a list of health outcomes of highest priority to examine in this context, and describes various study designs and statistical methods that could be used to analyze the safety of the schedule. While it appears feasible to study the safety of the recommended immunization schedule in settings such as the VSD, these studies will be inherently complex, and as with all observational studies, will need to carefully address issues of confounding and bias. In light of these considerations, decisions about conducting studies of the safety of the schedule will also need to assess epidemiological evidence of potential adverse events that could be related to the schedule, the biological plausibility of an association between an adverse event and the schedule, and public concern about the safety of the schedule.